(untitled) (University of Bucharest Review. Literary and Cultural Studies Series, 2024)
HBO’s five-episode docudrama Chernobyl (2019) is an attempt to re-imagine the horrific nuclear explosion of 1986 in Pripyat, and what it was like to live through the catastrophic tragedy. Throughout the extent of the show, the creators are seen attempting to strike a balance between the dramatization required for televisual representation and the effort to maintain historical accuracy. Subsequently, Chernobyl successfully portrays (and juxtaposes) two conflicting responses to the disaster of 1986 — the state-sanctioned denial and distortion of the real events incorporated by a series of self-serving officials, and the “personal evaluation” of first-hand witnesses — such as Valery Legasov, Boris Scherbina, and Ulana Khomyuk — configured to establish a counter-narrative to a state-monopolized history. Hence, Chernobyl becomes what Agnes Heller calls an ‘evaluative reconstruction’ of the 1986 disaster, making way for a historiographical study. This article will also attempt to illustrate how Craig Mazin and Johan Renck’s portrayal of the Chernobyl nuclear disaster opens up the possibility of critiquing the pre-existing unquestionability, and the imagined notions of power and perfection of the Soviet hierarchy, as is represented in the show by a set of corrupt government agents and servicemen working for the Ukrainian Soviet Socialist Republic.